2022
DOI: 10.1038/s41598-022-18943-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between bearing strengths of molded-in and machined holes of GFR/PP composites

Abstract: This study is an investigation of weight fraction (wt%) and fiber feedstock length (FFSL) effects on the bearing strength (BS) of bolted joints in glass-fiber-reinforced (GFR) polypropylene (PP) composites manufactured by an injection molding technique. The investigation was made for holes produced either by molding or machining. For machined holes, the effect of drilling parameters (feed and speed) on BS was discussed. It is observed that BS decreased as FFSL increased. BS of both molded-in and drilled specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…They reported that, when FFSL increases, both L n and L w increase for FFSL up to 9 mm, while for FFSL more than 9 mm both L n and L w decrease. More details including histograms for each weight fraction and FFSL was provided in previous study 43 . Throughout this work, based on the above results, FFSL of 12 mm and 24 mm will be referred to as "long fiber/Polypropylene (LFRPP)" and "short fiber/ Polypropylene (SFRPP)", respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that, when FFSL increases, both L n and L w increase for FFSL up to 9 mm, while for FFSL more than 9 mm both L n and L w decrease. More details including histograms for each weight fraction and FFSL was provided in previous study 43 . Throughout this work, based on the above results, FFSL of 12 mm and 24 mm will be referred to as "long fiber/Polypropylene (LFRPP)" and "short fiber/ Polypropylene (SFRPP)", respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More details including histograms of the fiber lengths were discussed in a previous study. 57 Throughout this work, based on the above results, FFSL of 12 mm and 24 mm will be referred to as "Long Fiber Reinforced Polypropylene (LFRPP)" and "Short Fiber Reinforced Polypropylene (SFRPP)," respectively.…”
Section: Actual Weight Fractionsmentioning
confidence: 99%
“…Glass fiber reinforced polymer matrix (GFRP) composites laminates are widely used in the aerospace, automotive, and marine industries, where drilling is typically required for subsequent component assembly. 1 However, drilling GFRP laminates typically results in burrs, splintering, and microcracks inside the GFRP structure in addition to delamination, fiber pull-out, and thermal degradation of the polymer matrix. [2][3][4][5] Additionally, the continuity of the fibers is lost as the GFRP in the hole region is being cut out, causing a significant stress concentration due to metallic inserts.…”
Section: Introductionmentioning
confidence: 99%